Surgical management of middle ear cholesteatoma in children with Turner syndrome: a multicenter experience - Zanetti, Diego; Di Lella, Filippo; Negri, Maurizio; Vincenti, Vincenzo (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: As in other syndromes characterized by craniofacial anomalies, middle ear cholesteatoma is known to have a high prevalence in Turner syndrome. The aim of this study was to review a multicenter experience with the surgical management of middle ear cholesteatoma in children with Turner syndrome. Methods: We retrospectively analyzed sixteen girls with Turner syndrome who underwent otologic surgery for middle ear cholesteatoma between January 2000 and December 2012. Surgery was performed in 3 tertiary care otologic centers. Four patients had bilateral disease, resulting in a total of 20 ears treated. The following data were recorded: age, history of ventilation tube insertion, status of the controlateral ear, cholesteatoma location and extension, and surgical technique involved. Cholesteatoma recidivism, stable mastoid cavity and hearing levels were the main outcomes measured. Results: Follow-up ranged from 3 to 15 years (mean 7 years). Fourteen ears underwent canal wall down mastoidectomy: no cases of recurrent cholesteatoma were observed in these cases; revision mastoidectomy with cavity obliteration was needed in 2 ears (14.3%) for recurrent otorrhea. In the remaining 6 ears a staged canal wall up mastoidectomy was performed: 1 child showed a recurrent cholesteatoma and required conversion to canal wall down mastoidectomy. A postoperative air-bone gap result of 0 to 20 dB was achieved in 6 ears (30%); in 9 ears (45%) postoperative air-bone gap was between 21 and 30 dB, while in 5 (25%) was >30 dB. Bone conduction thresholds remained unaffected in all cases. Conclusions: Cholesteatoma in children with Turner syndrome is a challenging entity for the otologic surgeon. Although not mandatory, canal wall down mastoidectomy should be regarded as the technique of choice to achieve a safe and dry ear in TS children with middle ear cholesteatoma. Intact canal wall mastoidectomy should be adopted only in appropriately selected patients such as those with limited attic cholesteatoma that can be regularly followed-up.